Application of criminal law in dealing with criminal acts against fiduciary guaranteses controlled by third parties in Federal International Finance Yogyakarta - Christo Arvian; Sudiyana Sudiyana; Eko Nurhayanto (Universitas Janabadra, 2020)
Along with economic growth, the needs of the community for goods and services are increasing as well as varying. While not all people can meet their needs with cash purchases. This opens up business opportunities for non-bank financial institutions, namely leasing. This thesis explains in full the legal coverage in dealing with criminal fiduciary guarantees against fiduciary guarantees that are controlled by third parties, and implementation or protection supporting the law of the creditors in dealing with Fiduciary claims against fiduciary guarantees controlled by parties. juridical empirical. Sources of data in this study were obtained from primary data and secondary data. This research uses sociological juridical. Data collected from PT FIF Yogyakarta and library research are then analyzed qualitatively. Research data after it has been conducted using qualitative methods, The research results are carried out following the Criminal Procedure in Fiduciary Assurance transferred to a third party will be given the following policies: Reporting to Fiduciary parties or supervisors in accordance with article 35 and article 36 of the Law law Number 42 of 1999 so that the second party follows up from the FIF Astra Yogyakarta after the FIF investigates the second party to settle Article 21 paragraph . PT FIF will settle the dispute. First done by giving a reprimand, then sent by giving a letter to the debtor, but if the debtor still does not fulfill it then the creditor takes the next action, namely through non-litigation and litigation method.